The Role of Accountability and Transparency in Advancing Meritocracy in the Selection of State Officials - Pratiwi, Kurnia; Yopan, Muhammad (Golden Ratio of Law and Social Policy Review, 2025)
In Indonesia, the meritocracy system is implemented through various bureaucratic reforms and human resource management in the public sector to overcome nepotism and primordialism. One of the primary keys in human resource management is the selection process, which can create professional Human Resources (HR). The strategy of the selection process must be based on qualifications to get the best candidates as a form of application of meritocracy. The application of meritocracy in the selection process is not only in attracting State Civil Apparatus, but also for selection in attracting and selecting State Officials. To get the best candidate, whose process is more acceptable to the public, as it can increase transparency and accountability by organizing a selection process. This study provides an example of how the accountability and transparency of meritocracy-based selection can be applied in organizing the selection of state officials. This research uses descriptive qualitative research methods with data analysis using research data sourced from interviews with informants, consisting of the secretariat of the selection committee and candidates for state officials who take part in the selection and document studies. The research results provide valuable insights into studies related to the organization of selection, especially State Officials, both inside and outside Indonesia.